Effects of foam rolling and dynamic stretching on balance, flexibility and agility in competitive women soccer players - Nurhannah Qistina Roslan (Nanyang Technological University, 2022)
Foam rolling (FR) has been described as a critically acclaimed topic with plenty of evidence on its effectiveness. Meanwhile, dynamic stretching (DS) is typically adopted as warm-up routines prior to trainings and matches. However, little is known about the combined effects of FR and DS on the performance of soccer players in terms of balance, flexibility, agility (BFA) and a soccer-specific circuit, especially in female athletes. PURPOSE. This study examines if a protocol of FR followed by the standard DS (FRDS) is more superior to a DS only warm-up protocol to improve the performance of BFA and a soccer-simulation circuit in female soccer players in Singapore. METHOD. This study adopts a randomised crossover approach with a within subject design. 17 competitive female soccer players (22  2.6 years) were recruited to participate both interventions (FRDS and DS only). Balance was assessed by Y-balance test, flexibility was measured using Sit-and-reach test, agility was assessed with the Modified T-test and a soccer simulation circuit was used to measure soccer-specific performance. RESULTS. The DS only group performed better than the FRDS group for the right leg balance (t(16) = -3.492, p < 0.05, r = 0.66, d = .85) and flexibility component (t(16) = -2.16, p < 0.05, r = 0.48, d = .52). There were no other significant effects found. CONCLUSIONS. FR did not seem to provide an improving effect in the BFA and soccer specific performance in female soccer players in Singapore.